2009
DOI: 10.1021/bi802335s
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Anthranilate Phosphoribosyltransferase from Sulfolobus solfataricus by Removal of Magnesium Inhibition and Acceleration of Product Release,

Abstract: Anthranilate phosphoribosyltransferase from the hyperthermophilic archaeon Sulfolobus solfataricus (ssAnPRT) is encoded by the sstrpD gene and catalyzes the reaction of anthranilate (AA) with a complex of Mg(2+) and 5'-phosphoribosyl-alpha1-pyrophosphate (Mg.PRPP) to N-(5'-phosphoribosyl)-anthranilate (PRA) and pyrophosphate (PP(i)) within tryptophan biosynthesis. The ssAnPRT enzyme is highly thermostable (half-life at 85 degrees C = 35 min) but only marginally active at ambient temperatures (turnover number a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…In agreement with this concept, rational protein design and directed evolution have shown that enzyme mutants with reduced stability often exhibit improved catalytic activity compared to the wild-type form, even though structural alterations are often minimal or u Nde tectable (e.g. [33], [34]). The lack of notable structural differences between the Kisumu 2B and ZAN/U 1C variants and the intrinsic dynamics of the region vicinal to the catalytic site in GSTE2 enzymes led us to speculate an effect of the residue exchanges in protein stability.…”
Section: Discussionmentioning
confidence: 82%
“…In agreement with this concept, rational protein design and directed evolution have shown that enzyme mutants with reduced stability often exhibit improved catalytic activity compared to the wild-type form, even though structural alterations are often minimal or u Nde tectable (e.g. [33], [34]). The lack of notable structural differences between the Kisumu 2B and ZAN/U 1C variants and the intrinsic dynamics of the region vicinal to the catalytic site in GSTE2 enzymes led us to speculate an effect of the residue exchanges in protein stability.…”
Section: Discussionmentioning
confidence: 82%
“…In an attempt to rationalize the poor catalytic proficiency of sAnPRT at ambient temperature, the activated D83G+F149S double mutant was isolated from a plasmid‐encoded s trp D gene library by metabolic complementation of an auxotrophic E. coli Δ trp D strain. Steady‐state and transient kinetic analysis showed that the D83G mutation leads to the removal of the inhibition of the wild‐type enzyme by high concentrations of Mg 2+ , whereas the F149S mutation results in accelerated release of the product PRA, which is the rate‐limiting step in the reaction of wild‐type sAnPRT 24. The observed decrease in ${T{{{\rm app}\hfill \atop {\rm M}\hfill}}}$ to 82 °C suggested that the diffusion of the product from the active site is facilitated by an increased conformational flexibility caused by the F149S mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Turnover rates as a function of PRPP concentration were obtained in the presence of saturating concentrations of the second substrate anthranilate, and Michaelis‐Menten parameters k cat and K M PRPP were deduced from saturation curves. The inhibitory effects of Mg 2+ concentrations >50 μM, as described for ss AnPRT, were not observed for other AnPRT variants; therefore, Mg 2+ concentration in the activity assays was set to 2 mM. In summary, steady‐state kinetic measurements substantiated that all AnPRT variants are active enzymes.…”
Section: Resultsmentioning
confidence: 99%